Augmented reality based application for chemistry education (ARCHEM) / Sia Wan Ling ... [et al.] - Sia, Wan Ling; Samsudin, Noor Azah; Aripin, Muhammad Syariff; Ahmad Khalid, Shamsul Kamal (Universiti Teknologi MARA, Kedah, 2019)
This project is about developing a learning application using augmented reality approach for Chemistry education at secondary school, also referred to as ARCHEM. The ARCHEM is built on Android based platform to facilitate users, especially students to interact with the learning content. The content of the ARCHEM includes essential topics in Chemistry subject such as periodic table and reactions of chemical elements. The interface of the periodic table is equipped with virtual buttons that allow students to view detail information of the Chemistry elements. Indeed, students can organize their self-learning activities at home or anywhere independently. The ARCHEM is expected to provide students a more interactive study experience. Essentially, the ARCHEM has demonstrated the benefit of utilizing mobile technology for educational activity. The ARCHEM will attract educators and students to consider a new way of learning instead of depending on textual based notes and offline classes only.